2019
DOI: 10.1111/mcn.12789
|View full text |Cite
|
Sign up to set email alerts
|

Commercially produced complementary foods in Bandung City, Indonesia, are often reported to be iron fortified but with less than recommended amounts or suboptimal forms of iron

Abstract: Commercially produced complementary foods (CPCF) that are iron fortified can help improve iron status of young children. We conducted a review of 217 CPCF sold in 42 stores in Bandung, Indonesia, in 2017. There were 95 (44%) infant cereals, 71 (33%) snacks or finger foods (biscuits or cookies, puffs, and noodles or crackers), 35 (16%) purees, and 16 (7%) other foods for which we obtained label information. Nearly 70% of CPCF reported iron content on their labels, but only 58% of products were reported to be fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The WHA Resolution 69.9 states that, “foods for infants and young children that are not products that function as breast‐milk substitutes should be promoted only if they meet all the relevant national, regional and global standards for composition, safety, quality and nutrient levels and are in line with national dietary guidelines” (WHO, ). This guidance presumes that products are fortified with both the appropriate amounts and types of nutrients, which is an area of investigation and legislation where the Indonesian government needs to engage in order to fulfil the WHA guidance (Dreyfuss et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The WHA Resolution 69.9 states that, “foods for infants and young children that are not products that function as breast‐milk substitutes should be promoted only if they meet all the relevant national, regional and global standards for composition, safety, quality and nutrient levels and are in line with national dietary guidelines” (WHO, ). This guidance presumes that products are fortified with both the appropriate amounts and types of nutrients, which is an area of investigation and legislation where the Indonesian government needs to engage in order to fulfil the WHA guidance (Dreyfuss et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The iron content of 217 complementary foods sold in stores included in the Bandung City study (Hadihardjono et al, ) was assessed by Dreyfuss et al () through a review of labels on 95 infant cereals, 71 snacks/finger foods (biscuits/cookies, puffs, and noodles/crackers), 35 purees, and 16 other foods. The recommended age of use on product labels varied by the type of product; most (81%) cereals were recommended for use beginning at 6 months of age, while 60% of snacks/finger food, 70% of pureed food, and 100% of mixed meals and pudding were recommended for use starting at 1 year of age.…”
Section: Understanding Nutrient Content Of Commercial Foods Commonly mentioning
confidence: 99%
“…Nonetheless, data on the iron content and fortification status of these products are scarce. An Indonesian study examined iron content of local and imported commercial pre‐packaged baby foods, and found that 58% were iron fortified 14 . This revealed much higher proportions of iron fortification in infant foods available in Indonesia compared with our Hong Kong sample, where only <20% of all pre‐packaged baby foods were iron‐fortified.…”
Section: Discussionmentioning
confidence: 69%
“…We also further examined the presence of iron‐related guidelines/cautions on the packages, a novel data type not previously reported by similar studies. Lastly, we followed the classification by Dreyfuss et al 14 which enabled comparability of our results with their study.…”
Section: Discussionmentioning
confidence: 87%